PENGARUH PEMBERIAN BEBERAPA JENIS MULSA ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI SEMANGKA (Citrullus vulgaris L) - Yosiana Sri Wulandari; Armaini Armaini; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The aim of this experiment was to determine the effect of some organic mulch application and to find the best type of organic mulch for increase growth and yield of watermelon. This research had been conducted at field of UPT Faculty of Agriculture, University of Riau, from September to November 2015. The experiment unit arrangd in a randomized block design with four treatment and five replication, so to find 20 plot of experiment. The given treatment is organic mulch application (M) is: M0: without organic mulch, M1: rice husk mulch 6 kg/plot (5 ton/ha), M2: maize stover mulch 6 kg/plot (5 ton/ha), M3: put sawdust mulch 6 kg/plot (5 ton/ha). Parameters observed were plant’s height, ring trunk, flower age, horizontal and vertikal ring, watermelon’s weight and yield. Data were analyzed using analysis of variance and continued with Duncan’s New Multiple Range Test (DNMRT) at 5% level. The results showed organic mulch application on watermelon did not have any effect plant’s height, ring trunk, flower age, horizontal and vertikal ring, but drastically reduced on increasing of watermelon’s weight and yield. The rice straw mulch is the best of organic mulch drastically reduced plant’s height, ring trunk, flower age, horizontal and vertikal ring and watermwlon’s weight. Rice straw mulch drastically reduced the yield is 14,32 ton/ha. Keywords : organic mulch, rice husk, maize stover, put sawdust